Fossil crinoids from the basal West Point Formation (Silurian), southeastern Gaspé Peninsula, Québec, eastern Canada - Donovan, Stephen; Keighley, David (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2016)
ABSTRACT Silurian strata of Atlantic Canada and southern Québec locally preserve common fossil crinoids, albeit mostly as disarticulated remains. New crinoids from the Chaleurs Group, West Point Formation (Ludlow to Pridoli?; Upper Silurian) of the Gaspé Peninsula include Iocrinus? maennili (Yeltysheva) (otherwise known from the Katian of Estonia), Bystrowicrinus (col.) depressus sp. nov. and Cyclocyclicus (col.) sp. aff. C. (col.) echinus Donovan. On the basis of both its gross morphology and stratigraphic position, Iocrinus? maennili is unlikely to be an iocrinid disparid, a family that became extinct at the end of the Ordovician. The trivial name has hitherto been erroneously spelled as männili, mannili and mjannili. Most specimens of the common Bystrowicrinus (col.) depressus appear cyclocyclic because the pentastellate lumen occurs in a deeply sunken claustrum that is commonly occluded by sediment; clean specimens are highly distinctive. Cyclocyclicus (col.) sp. aff. C. (col.) echinus is similar to a species known from the Katian of North Wales. Taken together, this assemblage is more reminiscent of Katian strata (Upper Ordovician). This is problematic given the current mapping of the outcrop as West Point Formation (Upper Silurian), suggesting further stratigraphic studies in the area are required.